Victims‘ rights: The European court of human rights' practice and legislation in Serbia - Kovačević Milica (Temida)
The paper deals with rights and position of victims in international documents, with special reference to the standards created by the European Court of Human Rights through its practice. This paper aims to provide brief analysis of some of the most important international documents, which set forth basic rights for victims, including: right to participate in the criminal proceedings, right to protection and the right to compensation. The paper intends to analyze these key right (standards, principles) through relevant case law of the European Court of Human Rights, given that the wording of the relevant documents does not determine what entails the realization of a specific standard in real life. The main purpose of the article is to examine the compliance of regulations and practices in Serbia with international standards on the status and the rights of victims, from which some recommendations for improvement might arise. [Projekat Ministarstva nauke Republike Srbije, br. 179044: Razvoj metodologije evidentiranja kriminaliteta kao osnova efikasnih mera za njegovo suzbijanje i prevenciju]